Metode Pemancangan Mini Pile dengan Vibratory Pile Driver yang Dimodifikasi - Hari Nugroho Akimas; Darmansyah Tjitradi (Jurnal Teknologi Berkelanjutan, 2022)
Infrastructure development in Banjarmasin is growing rapidly, this can be seen by the number of construction projects for shop houses, warehouses, housing and other civil buildings, both by government institutions, private sector and individuals. The type of soil in Banjarmasin is soft soil which has a very low bearing capacity, so generally the building foundation uses gelam wood. But now gelam wood is getting rare and expensive. To answer the scarcity of gelam wood, the mini pile concrete foundation could become an alternative solution. Mini pile erection using a modified Vibratory Pile Driver is an option for construction service providers with several advantages by minimizing some of the existing weaknesses. The advantages of this system are mainly in terms of cost, mobilization and adjustment of field conditions and are technically superior and safe in terms of the stability of the shop house foundation structure.